2017
DOI: 10.1371/journal.pone.0173771
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal adaptation: How cells respond to lysosomotropic compounds

Abstract: Lysosomes are acidic organelles essential for degradation and cellular homoeostasis and recently lysosomes have been shown as signaling hub to respond to the intra and extracellular changes (e.g. amino acid availability). Compounds including pharmaceutical drugs that are basic and lipophilic will become sequestered inside lysosomes (lysosomotropic). How cells respond to the lysosomal stress associated with lysosomotropism is not well characterized. Our goal is to assess the lysosomal changes and identify the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
119
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 49 publications
8
119
2
2
Order By: Relevance
“…In line with these observations, we did not find a decrease in LysoTracker Red-positive puncta upon CQ treatment as previously shown [29,[55][56][57]. Our results and other recent studies [30,58,59], indicate that CQ does not substantially decrease lysosomal acidity, and the lysosomes retain their capacity to degrade delivered material. Although we cannot exclude that CQ treatment has a different effect on lysosomal pH depending on the cell type, one has to be careful in interpreting signal intensities of LysoTracker Red.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with these observations, we did not find a decrease in LysoTracker Red-positive puncta upon CQ treatment as previously shown [29,[55][56][57]. Our results and other recent studies [30,58,59], indicate that CQ does not substantially decrease lysosomal acidity, and the lysosomes retain their capacity to degrade delivered material. Although we cannot exclude that CQ treatment has a different effect on lysosomal pH depending on the cell type, one has to be careful in interpreting signal intensities of LysoTracker Red.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, part of the discrepancy on CQ effects on lysosomal pH might be attributed to how the pH was estimated. Moreover, CQ may induce a temporal elevation of lysosomal pH [30,61], which is of a transient nature and is followed by a stable, lasting re-acidification of the lysosomes [30]. The kinetics of this transient phase may also differ from cell type to cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomal accumulation of uncatabolized material is a hallmark of a large number of diseases, including lysosomal storage disorders, Alzheimer's disease, Parkinson's disease, and brain aging (5)(6)(7). Moreover, it has been recently demonstrated that diverse lysosomotropic drugs accumulate within the lysosomes, affecting their function (8,9). However, the molecular mechanism responsible for the onset of cell damage upon lysosomal engulfment remains unknown to date; this represents the main challenge in the field.…”
mentioning
confidence: 99%
“…CQ is a well-established lysosomotropic compound, which, in its free base form, can easily traverse the lipid bilayer of the lysosome and become ionized in its lumen, thereby reducing its permeability (120). The accumulation of CQ in the lumen of the lysosome serves as a sink for free protons culminating in an increase in the lysosomal pH (121), an effect which works to normalize the hyperacidification of the lysosome in response to HDACi treatment.…”
Section: Discussionmentioning
confidence: 99%